IMMUNOMODULATORY ACTIVITY OF MESENCHIMAL STROMAL (STEM) CELLS - V. B. Klimovich (SPb RAACI, 2014)
Mesenchymal stromal or stem cells (MSC) represent a population of primitive fibroblastlike cells that are able to differentiate into cellular lineages of connective tissue (osteocytes, chondrocytes, adipocytes), skeletal muscles, and blood vessels. The review deals with contemporary views concerning descent, immunophenotype and immunogenicity of MSC. The studies over last decade revealed an ability of MSC to function as immunomodulatory populations which may suppress innate immunity factors (dendritic cells, natural killers, complement), as well as T-helpers and cytotoxic T-lymphocytes, along with activation of regulatory T lymphocytes (Treg). Special attention is given to analysis of conflicting data about influence of MSC on functions of B-lymphocytes and plasma cells in experimental settings, both in vitro and in vivo conditions. Data presently available are insufficient to explain the controversions revealed. In future investigations, it is necessary to consider attribution of B-cells to B1a, B1b, or B2 subpopulations as well as possible presence of poorly studied regulatory B-cells. It is also important also to take into account potential heterogeneity of initial MSC populations being isolated according to previously approved protocols. (Med. Immunol., 2014, vol. 16, N 2, pp 107-126)